Amputation of a major propulsor would not be an insuperable obstacle for survivorship of the slender sunfish Ranzania laevis (Molidae: Tetraodontiformes). (5th March 2014) - Romanov, Evgeny V.; Sharp, Alan; Bach, Pascal
Abstract : A record of a healthy specimen of slender sunfish Ranzania laevis with an amputated anal fin and healed scars is described from the south-western Indian Ocean. This is the first evidence of nektonic pelagic fish survival in spite of the ablation of a major locomotory organ and the first indication of non-lethal predation on adult slender sunfish.